2016
DOI: 10.1177/0884533616629619
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐Up Survey on Functionality of Nutrition Documentation and Ordering Nutrition Therapy in Currently Available Electronic Health Record Systems

Abstract: This is a call to action to nutrition support clinicians, societies, and organizations to proactively be involved in initiatives to educate clinicians and collaborate with EHR vendors to enhance the EHR systems to improve the safety and efficacy of providing nutrition therapy in hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Easy access to nutrition assessment data and outcome measures is an essential part of this process. In this survey, 97% of the respondents reported use of an EHR in some way (86% fully electronic and 11% a blend of electronic and paper documentation), which is an increase from a 2014 ASPEN survey where 90%–94% of clinicians used an EHR . Retrieving relevant documentation to validate the Academy/ASPEN malnutrition characteristics may be challenging due to the way clinical data are documented.…”
Section: Discussionmentioning
confidence: 96%
“…Easy access to nutrition assessment data and outcome measures is an essential part of this process. In this survey, 97% of the respondents reported use of an EHR in some way (86% fully electronic and 11% a blend of electronic and paper documentation), which is an increase from a 2014 ASPEN survey where 90%–94% of clinicians used an EHR . Retrieving relevant documentation to validate the Academy/ASPEN malnutrition characteristics may be challenging due to the way clinical data are documented.…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, adoption of EHRs and CDS to improve safety of the PN process has been limited. In recent surveys, only 33%–63% of respondents reported using an electronic order for PN and only 50%–54% utilized dosing guidelines and CDS built into the system . Furthermore, only about 28% of respondents reported that they had an automatic interface between the EHR and ACD at their institution …”
Section: Opportunities For Optimizing the Ehr In The Pn Workflowmentioning
confidence: 99%
“…The electronic medical record (EMR) allows clinicians to access data about nutrition anthropometrics, medical and surgical history, nutrition access devices, biochemical test results, and nutrition programs. However, surveys have noted a significant need for improvement of nutrition content in available EMRs, prompting a call to action to nutrition support clinicians and societies to work collaboratively with vendors 94 . For 20 years, we have used an EMR that integrates into 1 report computerized data from laboratory, microbiology, radiology, and operative report sources, along with nutrition anthropometrics and PN pharmacy data.…”
Section: Electronic Medical Recordmentioning
confidence: 99%